2010
DOI: 10.1038/nn.2702
|View full text |Cite
|
Sign up to set email alerts
|

Retinoid X receptor gamma signaling accelerates CNS remyelination

Abstract: The molecular basis of CNS myelin regeneration (remyelination) is poorly understood. We generated a comprehensive transcriptional profile of the separate stages of spontaneous remyelination that follow focal demyelination in the rat CNS and found that transcripts that encode the retinoid acid receptor RXR-γ were differentially expressed during remyelination. Cells of the oligodendrocyte lineage expressed RXR-γ in rat tissues that were undergoing remyelination and in active and remyelinated multiple sclerosis l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
483
3
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 472 publications
(509 citation statements)
references
References 41 publications
16
483
3
7
Order By: Relevance
“…RXRγ was recently identified as a factor regulating myelination in a microarray analysis of separate stages of spontaneous remyelination after focal demyelination in the rat CNS [28] . RXRγ is highly expressed in remyelinating lesions, suggesting that it may be important in lesion repair.…”
Section: Retinoid X Receptor-gammamentioning
confidence: 99%
See 1 more Smart Citation
“…RXRγ was recently identified as a factor regulating myelination in a microarray analysis of separate stages of spontaneous remyelination after focal demyelination in the rat CNS [28] . RXRγ is highly expressed in remyelinating lesions, suggesting that it may be important in lesion repair.…”
Section: Retinoid X Receptor-gammamentioning
confidence: 99%
“…This was further investigated by gain/loss-of-function studies in purified OPC and cerebellar slice cultures. Knockdown of RXRγ by RNA interference or RXR-specific antagonists severely inhibits oligodendrocyte differentiation in culture, while the RXR agonist 9-cis-retinoic acid promotes remyelination in demyelinated cerebellar slice cultures and in demyelinated aged rats [28] . However, given the pleiotropic roles of RXRγ and its diverse partners, a general RXRγ agonist may have significant side effects.…”
Section: Retinoid X Receptor-gammamentioning
confidence: 99%
“…Analysis of gene expression profiles during development in the normal adult brain and during demyelination identified several novel regulatory pathways of oligodendrocyte differentiation. These studies showed that oligodendrocyte differentiation and remyelination are dependent on retinoid-X receptor-gamma receptor agonists [115] and on Wnt-beta-catenin signaling [116]. In addition, type 2 cyclin dependent kinase (also known as cdk2), which controls the cell cycle, does not interfere with myelination during development, but its knock-out facilitates remyelination [117].…”
Section: Myelin Regeneration Fails In Msmentioning
confidence: 99%
“…Recent reports suggest that demyelination in experimental allergic encephalomyelitis (EAE) is related to an increase in ApoE 25, which supports the present findings. In addition, retinoid acids (rxrs) are essential for cholesterol metabolism 27, 28 and stimulate oligodendrocyte differentiation 29. Interestingly, we found that 0.5 mg/kg of WIN during CPZ exposure increased the expression of Rxra which might protect myelinated axons against cuprizone.…”
Section: Discussionmentioning
confidence: 86%